Pilihan Media Pencari Informasi Kesehatan - Rizanna Rosemary (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
The number of smokers among women in Indonesia is increasing every year, even though smokers are predominantly male. In order to educate the public about the negative impacts of tobacco consumption, the government has produced anti-smoking Public Service Advertisements (PSAs) aired on television. The information gap about smoking hazards is due to lack of anti-smoking messages which is unable to compete with the extensive and creative pro-smoking messages in many media platforms. The way people use media for information-seeking, such as messages about smoking, dictates how they look for the messages and helps to understand how they encounter messages the most. By interviewing 39 women in Banda Aceh and Jakarta, this study presents women’s opinion about television and the media preference for searching and gaining information about smoking. The findings show that participants of the study prefer to obtain information about smoking through the media—online social media than through television, such as Facebook, YouTube, Instagram, Line, WhatsApp, and non-media like friends and their doctor’s advice. Given the substantial cost of television health campaigns, the study findings can provide input on alternative media in communicating about the harms of smoking.